1994
DOI: 10.1016/s0944-7113(11)80025-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant adaptogens

Abstract: The term adaptogen has not yet been accepted in medicine. This is probably due to the difficulties in discriminating adaptogenic drugs from immunostimulators, anabolic drugs, nootropic drugs, and tonics. There can be not doubt, however, that, at least in animal experiments, there are plant drugs capable of modulating distinct phases of the adaptation syndrome as defined by Seyle. These drugs either reduce stress reactions in the alarm phase or retard / prevent the exhaustion phase and thus provide a certain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
12

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 46 publications
1
101
0
12
Order By: Relevance
“…The ability of adaptogens to increase work capacity and physical performance has often been assessed using the swimming test in rodents, under different experimental conditions. Indeed, both adaptogens and antidepressants can increase the amount of time that an animal is able to keep swimming actively (Brekhman and Dardymov, 1968;Espinola et al, 1977;Banerjee and Izquierdo, 1982;Singh et al, 1988;Wagner et al, 1994;Dhuley, 2000;Abidov et al, 2003).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of adaptogens to increase work capacity and physical performance has often been assessed using the swimming test in rodents, under different experimental conditions. Indeed, both adaptogens and antidepressants can increase the amount of time that an animal is able to keep swimming actively (Brekhman and Dardymov, 1968;Espinola et al, 1977;Banerjee and Izquierdo, 1982;Singh et al, 1988;Wagner et al, 1994;Dhuley, 2000;Abidov et al, 2003).…”
Section: Drugsmentioning
confidence: 99%
“…rosea is used in traditional folk medicine to stimulate the nervous system, to decrease depression, to enhance work performance, longevity and resistance to high altitude sickness, and to treat fatigue and symptoms of asthenia subsequent to intense physical and psychological stress (Kelly, 2001;Brown et al, 2002;Zhu et al, 2003). Therefore, due to its ability to increase the resistance of an organism to environmental stress factors and to avoid damage from such factors, R. rosea has been defined as an 'adaptogen' (Wagner et al, 1994;Panossian et al, 1999;Panossian, 2003;Panossian and Wagner, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization has been the ideal choice for the induction of stress responses in animals and more specifically, for the investigation of drug effects, on typical stress-related gastrointestinal, neuroendocrine, and immunological pathology. Immobilization model used in our study found to cause long term desensitization of HPA response which affected both peripheral and central components of the HPA axis (Wagner., 1994). The distinct advantage of using immobilization as a stressor lies in the fact that it produces both physical as well as inescapable psychological stress (Krupavaram et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Extracts from the leaves of this plant could also exhibit in vivo adaptogenic related biological effects including anti-inflammatory and anti-anxiety activities. Polyphenolics and flavonoid, phytochemicals that play important role in antioxidation, anti-inflammatory and adaptogenic actions in plants (Hoorn, 2003, Panossian and Wagner, 2005, Wagner et al, 1994 were found to available in high amount in A. trifoliatus, especially in the leaves and the roots. Active polyphenolics and flavonoid compounds were structurally identified.…”
Section: Resultsmentioning
confidence: 99%
“…Some in vitro studies were also conducted such as antioxidative and anti-inflammatory effect experiments. Adaptogenic plants can promote anti-stress effects via several mechanisms including increasing of body temperature, improvements of body function, enhancing of cognitive abilities, promoting of locomotor and exploration activities, and moderating the emotional behavior (Wagner et al, 1994). Fig.…”
Section: Introductionmentioning
confidence: 99%